Research and Implementation of Congestion Control Scheme in ForCES Router - Bangzhi Xiao; Ming Gao; Weiming Wang; Julong Lan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With packet input rate rise ceaselessly, FoCES system will finally be congested. In order to solve this problem, aiming at the common local congestion and global congestion, this paper proposed a local congestion control strategy based on scheduling and a global congestion control mode based on the linkage between CE and FE. These two congestion control schemes can independently run inside the system, and also can operate simultaneously. Making that the forwarding rate, throughout and packet loss all have a great improvement in the FE end. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3387